Wolbachia infection modifies the profile, shuttling and structure of microRNAs in a mosquito cell line. - Jaime G Mayoral; Kayvan Etebari; Mazhar Hussain; Alexander A Khromykh; Sassan Asgari (PLoS ONE)
MicroRNAs (miRNAs) are small non-coding RNAs that play important roles in many biological processes such as development, cell signaling and immune response. Small RNA deep sequencing technology provided an opportunity for a thorough survey of the miRNA profile of a mosquito cell line from Aedes aegypti. We characterized the miRNA composition of the nucleus and the cytoplasm of uninfected cells and compared it with the one of cells infected with the endosymbiotic bacterium Wolbachia strain wMelPop-CLA. We found an overall increase of small RNAs between 18 and 28 nucleotides in both cellular compartments in Wolbachia-infected cells and identified specific miRNAs induced and/or suppressed by the Wolbachia infection. We discuss the mechanisms that the cell may use to shuttle miRNAs between the cytoplasm and the nucleus. In addition, we identified piRNAs that changed their abundance in response to Wolbachia infection. The miRNAs and piRNAs identified in this study provide promising leads for investigations into the host-endosymbiont interactions and for better understanding of how Wolbachia manipulates the host miRNA machinery in order to facilitate its persistent replication in infected cells.